A start-up of workers' communication platform in Japan - Kajitani, Tatsuya (2024)
The business plan aims to create a place where employees of Japanese companies can get ideas for their work. The value offered by the business is the ability to interact with people from outside the company who have different perspectives from their own, and to quickly have the opportunity to discuss issues they are facing. Specifically, the business model is that an online platform and an associated physical location is provided for discussions.